PENGARUH PENERAPAN PENDEKATAN METAKOGNITIF BERBASIS MASALAH TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Nur Fauziah Siregar (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
This study aims to identify the effect of implementing problem-based metacognitive approach to problem solving abilities of students in SMP Negeri 7 Padangsidimpuan. This research used a quasi-experimental method. The population of this study was all eighth grade students consisting of 6 classes with 137 students and the sample consisted of two classes, i.e. the experimental class of VIII-3 with 23 students and the control class of VIII-5 with 24 students, and this study used a simple random technique in choosing the samples. The instrument used was a test of problem solving ability. The data obtained were analyzed by using t test. Based on the normality and homogeneity test, both sample classes are normally distributed and homogeneous. From the calculation of hypothesis testing, it was obtained that the value of t count is 4.534, while the t table at the significant level of 5% is 2.014. So, this study obtained t count > t table (4.534 > 2.014). It means that the Ha Hypothesis is accepted which means there is the effect of implementing problem-based metacognitive approach to the problem solving ability of students.